Perfil clínico epidemiológico de pacientes adultos con bronquiectasia - Pérez Anticona, Jesús Miguel (2017)
To describe the clinical epidemiological profile of adults diagnosed with bronchiectasis. Material and method: The design used corresponds to a descriptive-transversal study. We reviewed 182 medical records of patients diagnosed with bronchiectasis at hospitals Belén and Regional of Trujillo during the period 2011-2014, which met the inclusion and exclusion criteria established. Results and conclusions: The epidemiological characteristics identified: age group over 50 years, mean age 61.2 ± 12.7 years; Male gender (65.9%); Agricultural occupation (28.6%), rural areas (61.0%), smoking (2%). In the etiology and / or antecedents, had tuberculosis (46.2%), the predominant type of inflammatory pneumonitis was aspiration (1.1%). 0.5% reported having a family history of bronchiectasis. In antecedent of infections, the bacteriana was the most found. Clinical characteristics identified: the most frequent sign was cough (85.7%), and as dyspnea symptom (81.3%). Local affection and cylindrical morphology. Comorbidity ACV followed by COPD